Analysis of Sedimentation Rate in the Air Sambat River, Kaur District Using the Meyer Peter Muller and Van Rijn Methods - Khairul Amri; Lindung Zalbuin Mase; Ade Mandala Putra (PT FORMOSA CENDEKIA GLOBAL, 2023)
Analysis Of Sedimentation Rate in The Sambat River Kaur Regency Using Meyer Peter Muller and Van Rijn. The Air Sambat River is located in Maje District, Kaur Regency, Bengkulu Province. The Air Sambat River is a community cultivation area, both in the river border line (GSS) area and in the water catchment area. The condition of the flow of the Air Sambat River is categorized as bad, during the dry season the water can recede drastically, and in the rainy season, it can cause flooding. The data obtained in the field are in the form of flow velocity, depth, and bedload samples. Therefore, this study was conducted to determine the type of sediment and determine the rate of bottom sediment transport in the Lower Air Sambat River in the Air Sambat River, Kaur Regency, Bengkulu Province. Research samples were tested in the laboratory to determine the type of soil and obtain data used for analysis. The analytical calculation method used in this research is the Meyer Peter Muller method and the Van Rijn method. The results showed that the Meyer-Peter Muller method was suitable to be used to describe the conditions of sediment deposition in the review area with a sedimentation rate of 3,057 × 105 tons/year